PENEGAKAN HUKUM TERHADAP PENCURIAN KENDARAAN BERMOTOR BERDASARKAN PASAL 362 KUHP DI WILAYAH KEPOLISIAN BANDAR LAMPUNG - Mansah .; Irfan Raihan Hady Fauzi; Arya Oktama (Peneliti.net, 2023)
Law enforcement is an attempt to express the moral image contained in the law. The rise of motor vehicle theft that is growing, the strategic location and ease of committing the crime of motor vehicle theft, and the difficulty of finding evidence of perpetrators by investigators make the crime of motor vehicle theft increasingly attractive to criminals. The formulation of the problem in this study is how to enforce the law against the crime of motor vehicle theft and what are the obstacles and how to enforce the law against the crime of motor vehicle theft. The research used is empirical research. The results of the study found that law enforcement against the crime of motor vehicle theft was carried out by following up on reports from victims of theft through the SPKT which were then made a BAP which was then carried out by an investigation and after completion the investigator handed over the suspect to the police and if it was not known or found a further examination was carried out and made DPO letter. Internal constraints faced include inadequate facilities and infrastructure, disconnected information networks, inadequate police officers, and inadequate budget support. Preventive efforts in the form of appeals to the public to be more careful, giving advice not to park vehicles carelessly and giving double keys. His repressive efforts carried out further investigations to uncover other perpetrators of motor vehicle theft.